Heteroleptic Cu(I) complexes with aromatic diimines and phosphines: Synthesis, structure, photophysical properties and THz time domain spectroscopy. (1st June 2019) - Kuang, Xiao-Nan; Lin, Sen; Liu, Jian-Ming; Han, Hong-Liang; Liu, Min; Xin, Xiu-Lan; Yang, Yu-Ping; Li, Zhong-Feng; Jin, Qiong-Hua; Li, Si-Fan; Li, Yue-Xue; Feng, Yue-Bing
Graphical abstract: Different copper(I) complexes were synthesized by changing the anions and ligands. All complexes show 0D−3D structures which are caused by intermolecular interactions such as hydrogen bonds, CH⋯π interactions and π⋯π interactions. The luminescence properties of complexes are generated by metal-to-ligand charge transfer (MLCT). In addition, THz time-domain spectroscopy was also studied in this research. Abstract: Nine novel copper(I) complexes with diphosphine and diimine ligands, namely [Cu(dpq)(xantphos)]BF4 (1 ), [Cu(dpq)(xantphos)]I (2 ), [Cu(dpq)(dppp)]BF4 (3 ), [Cu(dppz)(dppp)]BF4 (4 ), [Cu(dppz)(dppp)]I (5 ), [Cu(dppz)(pop)]I (6 ), [Cu(dpq)(pop)]I (7 ), [Cu(dpq)(pop)]Br (8 ), [Cu(dpq)(pop)]SCN (9 ) (dpq = pyrazino[2, 3-f][1, 10]phenanthroline, dppz = dipyrido[3, 2-a:2′, 3′-c]phenazine, xantphos = 9, 9-dimethyl-4, 5-bis(diphenylphosphanyl)xanthene, dppp = 1, 3-bis(diphenylphosphino)propane, pop = 1, 1′-[(Oxydi-2, 1-phenylene)]bis[1, 1-diphenylphosphine]), were characterized by single crystal X-ray diffraction, IR, elemental analysis, 1 H NMR, 31 P NMR, fluorescence spectra and terahertz time domain spectroscopy (THz-TDS). These nine complexes were synthesized by the reactions of copper salts, diimine ligands and various of P-donor ligands through one-pot method. Single crystal X-ray diffraction reveals that complex9 is of a simple mono-nuclear structure while complexes6 and7 are of dimer structures. For complex8, hydrogen bonds and CH⋯π interactions lead to the formation of a 1D infinite chain structure. Interestingly, complexes1 –5 show novel 2D or 3D network structures through CH⋯π interactions. In addition, complexes1 –3 and6 –9 exhibit interesting fluorescence in the solid state at room temperature. Among the nine complexes, complex1 shows the highest quantum yield up to 37% and the lifetime of1 is 6.0 μs. The terahertz (THz) time-domain spectra of these complexes were also studied.